E-096 Spontaneous spinal extramedullary hemorrhage and the diagnostic yield of spinal angiography. (22nd July 2018) - White, A; Roark, C; Case, D; Kumpe, D; Seinfeld, J
Abstract : Introduction: Spontaneous spinal extramedullary hemorrhage (SSEH) is a rare cause of acute back or radicular pain and, occasionally, spinal cord compression. Numerous etiologies have been implicated including anticoagulation, vasculitis, aneurysms and vascular malformations. However, the cause of many SSEHs is never determined. Diagnostic spinal angiography is often performed in these cases, though the diagnostic yield of this exam has yet to be validated. Methods: A retrospective review of a single academic institution's Neurovascular database spanning from 2011 to 2018 was performed to identify patients with SSEH who underwent spinal angiography following MRI in order to identify the source of hemorrhage. Results: Seventy-two patients underwent spinal angiography during the study period. Of these, 9 patients with SSEH were identified. Six female and 2 male patients were aged 29–70 (mean 48 years). One patient was undergoing anticoagulant therapy at the time of hemorrhage, while one patient had a history of systemic lupus erythematosus. All but 1 patient presented with acute symptoms. The most common presenting symptom was acute back pain (n=6) with radicular symptoms (n=4). One patient presented with acute paraplegia, and 1 patient presented only with signs of meningismus. The one patient that presented in a delayed fashion complained of chronic back pain following an acute onset 1 year prior. All patients underwent MRI, which failed to diagnose a source of hemorrhage prior to diagnostic spinal angiography. Five patients had MRI evidence of spinal cord compression. Diagnostic spinal angiography failed to reveal a potential source of SSEH in all but one patient, in which a pseudoaneurysm of uncertain significance was identified in the paraspinal tissue following laminectomy for hematoma evacuation. This patient was treated with coil embolization, though this may have represented an unrelated postoperative finding. Two additional patients underwent decompressive laminectomy with hematoma evacuation, while 6 were managed non-operatively. Hospital duration for the patients presenting acutely ranged from 5–50 days (mean 16.5); disposition following discharge included acute rehab (n=2), subacute rehab (n=2), and home (n=4). Most patients (n=6, 67%) returned to baseline function, 2 patients suffered bilateral lower extremity paralysis, and a single patient experienced mild residual unilateral lower extremity weakness. Conclusion: SSEH often occurs without a clear source evident on MRI. In these cases, diagnostic spinal angiography is often performed. However, in our experience, this study has rarely been helpful in demonstrating the etiology of SSEH. Disclosures: A. White: None. C. Roark: None. D. Case: None. D. Kumpe: None. J. Seinfeld: 2; C; Medtronic.